2007
DOI: 10.1037/0893-3200.21.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Demand-withdraw communication in severely distressed, moderately distressed, and nondistressed couples: Rigidity and polarity during relationship and personal problem discussions.

Abstract: This study investigated demand-withdraw communication among 68 severely distressed couples seeking therapy, 66 moderately distressed couples seeking therapy, and 48 nondistressed couples. Self-report and videotaped discussions replicated previous research, demonstrating that greater demand-withdraw during relationship problem discussions was associated with greater distress and that overall, wife-demand/husband-withdraw was greater than husband-demand/wife-withdraw. Results extended the conflict structure view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
2
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 28 publications
7
102
2
5
Order By: Relevance
“…The results of this study demonstrated a change in both symptoms of depression and attachment avoidance for males from T1 to T2, and the change was predicted by specific communication patterns. With regard to demand-withdraw communication, previous research has consistently demonstrated sex-differences, with females being more likely to demand and males being more likely to withdraw (Klinetob and Smith 1996), and these sex differences have been found to be especially likely in distressed relationships (Caughlin and Vangelisti 1999;Eldridge et al 2007). Bearing that in mind, it is possible that these results support those of Wei et al (2005), who found that detachment (i.e., withdrawal) mediates the relationship between avoidant attachment and depression.…”
Section: Predicting Change In Attachment and Depressionsupporting
confidence: 57%
“…The results of this study demonstrated a change in both symptoms of depression and attachment avoidance for males from T1 to T2, and the change was predicted by specific communication patterns. With regard to demand-withdraw communication, previous research has consistently demonstrated sex-differences, with females being more likely to demand and males being more likely to withdraw (Klinetob and Smith 1996), and these sex differences have been found to be especially likely in distressed relationships (Caughlin and Vangelisti 1999;Eldridge et al 2007). Bearing that in mind, it is possible that these results support those of Wei et al (2005), who found that detachment (i.e., withdrawal) mediates the relationship between avoidant attachment and depression.…”
Section: Predicting Change In Attachment and Depressionsupporting
confidence: 57%
“…Partners may look at each other more consistently as a result of being entrenched in a negative state and unable to interact more randomly across a variety of states, as is more often the case with less negative, more satisfied couples. Additionally, the demand-withdraw pattern becomes more predominant in couples' interaction as distress increases (Eldridge et al 2007). Increased looking at one's spouse thus could be a nonverbal indicator of rigidity related to negative affect and the demand-withdraw pattern.…”
Section: Looking-behaviormentioning
confidence: 97%
“…Many lab study results are consistent with the clinical observations of couples' pursuer-distance process, especially those reported by Fogarty (1979). Eldridge, Sevier, Jones, Atkins, and Christensen (2007) found that, while both male and female partners employ demand and withdraw behaviors, the typical female-demand /male-withdraw pattern was more frequent in the distressed group.…”
Section: Pursuer-distancer Processmentioning
confidence: 97%